From Hand to Mouth: Women and Piecework - Armstrong, Pat (Labour / Le Travail, 1983)
This article reviews the book, "From Hand to Mouth: Women and Piecework," by Marianne Herzog.

Patterns of Belief and Action: Measurement of Student Political Activism - Axelrod, Paul (Labour / Le Travail, 1983)
This article reviews the book, "Patterns of Belief and Action: Measurement of Student Political Activism," by S.L. Sutherland.

Conscience and Convenience: The Asylum and its Alternatives in Progressive America - Baehre, Rainer (Labour / Le Travail, 1983)
This article reviews the book, "Conscience and Convenience: The Asylum and its Alternatives in Progressive America," by David J. Rothman.

Clifford Sifton, Vol. I: The Young Napoleon 1861-1900 - Baker, William M. (Labour / Le Travail, 1983)
This article reviews the book, "Clifford Sifton, Vol. I: The Young Napoleon 1861-1900," by D.J. Hall.

From Orthodox Marxism to Parliamentary Democracy: New Interpretations of the German Social Democratic and Labour Movement, 1880-1933 - Bassler, Gerhard P. (Labour / Le Travail, 1983)
The article reviews and comments on "Karl Kautsky and the Socialist Revolution 1880-1938," by Massimo Salvadori, "Karl Kautsky, 1854-1938: Marxism in the Classical Years," and "German Socialism and Weimar Democracy," by Richard Breitman.

Working-Class Capitalism in Great Britain and Canada, 1867-1914 - Benson, John (Labour / Le Travail, 1983)
Examines working-class "penny capitalism" in Great Britain and Canada from 1867-1914. Argues that such small, full time (or nearly full time) self-employed producers, often working from home, were a substantial presence in working-class families, as were part-timers, although the latter had mostly a defensive function. Further, penny capitalists, with their petty bourgeois aspirations of social mobility, were inimical to working class homogeneity. Concludes that penny capitalists contributed to the forces of industrialization through their impact on employment, purchasing power, and economic restructuring, as well as meeting, at least to some extent, the local demand for goods and services.

The Making of the East End Community Club - Black, Errol; Black, Tom (Labour / Le Travail, 1983)
Documents the socialist, working-class immigrant origins of the East End Community Club, which opened as a community-owned recreational centre in Brandon, Manitoba, on Labour Day, 1944. Includes illustrations and an appendix. The paper is adapted from "From Frozen Ponds: The East End Community Club," Brandon, East End Centennial Reunion Committee, 1982.

Class. Politics, and Early Industrial Capitalism: A Study of Mid-Nineteenth Century Toulouse, France - Borghese, Arthur (Labour / Le Travail, 1983)
This article reviews the book, "Class. Politics, and Early Industrial Capitalism: A Study of Mid-Nineteenth Century Toulouse, France," by Ronald Aminzade.

"A Good Poor Man's Wife": Being a Chronicle of Harriet Hanson Robinson and Her Family in Nineteenth Century New England - Brandt, Gail Cuthbert (Labour / Le Travail, 1983)
This article reviews the book, "'A Good Poor Man's Wife': Being a Chronicle of Harriet Hanson Robinson and Her Family in Nineteenth Century New England," by Claudia L. Bushman.

Inequality: Essays on the Political Economy of Social Welfare - Braybrooke, David (Labour / Le Travail, 1983)
This article reviews the book, "Inequality: Essays on the Political Economy of Social Welfare," edited by Allan Moscovitch and Glenn Drover.

The Working Poor, Wage Earners And The Failure Of Income Security Policies - Buchbinder, H. (Labour / Le Travail, 1983)
This article reviews the book, "The Working Poor, Wage Earners And The Failure Of Income Security Policies," by David P. Ross.

Marx's Theory of Politics - Burns, S.A.M. (Labour / Le Travail, 1983)
This article reviews the book, "Marx's Theory of Politics," by John M. Maguire.

One-Dimensional Marxism - Burns, S.A.M. (Labour / Le Travail, 1983)
This article reviews the book, "One-Dimensional Marxism," edited by Simon Clarke.

The Future of Socialism in Europe? = L'Avenir du socialisme en Europe ? - Burridge, Trevor (Labour / Le Travail, 1983)
This article reviews the book, "The Future of Socialism in Europe? = L'Avenir du socialisme en Europe ?," by André Liebich.

Dix ans de pratiques syndicales - Charland, Jean-Pierre (Labour / Le Travail, 1983)
This article reviews the book, "Dix ans de pratiques syndicales," by Louise Clermont-Laliberté.

Canadian Library Journal - Chisamore, Dale (Labour / Le Travail, 1983)
This article reviews the book, "Canadian Library Journal," by Peter McNally, ed.

Women, Work, and National Policy: The Kennedy-Johnson Years (Studies in American History and Culture, No. 33) - Cohen, Marjorie (Labour / Le Travail, 1983)
This article reviews the book, "Women, Work, and National Policy: The Kennedy-Johnson Years," by Patricia G. Zelman.

Entering the Eighties: Canada in Crisis - Craven, Paul (Labour / Le Travail, 1983)
This article reviews the book, "Entering the Eighties: Canada in Crisis," edited by R. Kenneth Carty and W. Peter Ward.

Women of the Republic: Intellect and Ideology in Revolutionary America - Crowley, Jack (Labour / Le Travail, 1983)
This article reviews the book, "Women of the Republic: intellect and Ideology in Revolutionary America," by Linda K. Kerber.

Marx and History: Front Primitive Society to the Communist Future - Cunningham, Frank (Labour / Le Travail, 1983)
This article reviews the book, "Marx and History: Front Primitive Society to the Communist Future," by D. Ross Gandy.

Popular Culture and Class Conflict. 1590-1914: Explorations in the History of Labour and Leisure - DeLottinville, Peter (Labour / Le Travail, 1983)
This article reviews the book: "Popular Culture and Class Conflict. 1590-1914: Explorations in the History of Labour and Leisure," edited by Eileen and Stephen Yeo.

Transatlantic industrial Revolution: The Diffusion of Textile Technologies between Britain and America, 1790-1830s - Delottinville, Peter (Labour / Le Travail, 1983)
This article reviews the book, "Transatlantic industrial Revolution: The Diffusion of Textile Technologies between Britain and America, 1790-1830s," by David J. Jeremy

Arguments Within English Marxism; The Making of E.P. Thompson: Marxism, Humanism, and History - Donnelly, F. K. (Labour / Le Travail, 1983)
This article reviews two books: "Arguments Within English Marxism," by Perry Anderson, and "The Making of E.P. Thompson: Marxism, Humanism, and History," by Bryan D. Palmer.

Towards the Planned City: Germany, Britain, The United States and France, 1780-1914 - Doucet, Michael J. (Labour / Le Travail, 1983)
This article reviews the book, "Towards the Planned City: Germany, Britain, The United States and France, 1780-1914," by Anthony Sutcliffe.

The Road to Gdansk: Poland and the U.S.S.R. - Dowler, Wayne (Labour / Le Travail, 1983)
This article reviews the book, "The Road to Gdansk: Poland and the U.S.S.R.," by Daniel Singer.

Civilization and Capitalism, 15th-18th Century, Volume I: The Structures of Everyday Life - English, Christopher (Labour / Le Travail, 1983)
This article reviews the book, "Civilization and Capitalism, 15th-18th Century, Volume I: The Structures of Everyday Life," revised edition, by Fernand Braudel.

Joe McCarthy and the Press - English, John (Labour / Le Travail, 1983)
This article reviews the book, "Joe McCarthy and the Press," by Edwin R. Bayley.

Punishment and Penal Discipline: Essays on the Prison and the Prisoners' Movement - Fink, Leon (Labour / Le Travail, 1983)
This article reviews the book, "Punishment and Penal Discipline: Essays on the Prison and the Prisoners' Movement," edited by Tony Piatt and Paul Takagi.

Rockefeller Medicine Men: Medicine and Capitalism in America - Fink, Leon (Labour / Le Travail, 1983)
This article reviews the book, "Rockefeller Medicine Men: Medicine and Capitalism in America," by E. Richard Brown.

The "Ingredients" in Violent Labour Conflict: Patterns in Four Case Studies - Frank, J. A. (Labour / Le Travail, 1983)
The article endeavours to gain some insights into the dynamics of violent labour conflicts, by examining four case studies and highlighting certain factors deemed significant in all four. The cases studied are the Robin Hood flour mill strike of 1977, the Fleck Manufacturing strike in 1978, the Murray Hill conflict in 1969, and the Artistic Woodwork strike of 1973. In examining these conflicts, four aspects were emphasized as important determinants in their outcomes: the organization and relative power of the strikers, the attitude of their adversaries (how they were perceived), the aims that the workers pursued, their style of collective action, and above all the policies and power of the employers and the authorities. In the concluding portion of the paper the interaction between these factors was examined to see how they influenced the outcome of each incident, this as an empirical preliminary to theory building.

Strangers in Blood. Fur Trade Company Families in Indian Country - Friesen, Jean (Labour / Le Travail, 1983)
This article reviews the book, "Strangers in Blood. Fur Trade Company Families in Indian Country," by Jennifers.H. Brown.

Australian Labour and Labour History - Fry, Eric (Labour / Le Travail, 1983)
Introduces the labour, economic and political history of Australia, including the Australian Labor Party, which came to government prior to WWI, and focuses on the historiographical patterns that emerged on labour history. Discusses pioneering studies and the founding of Australian Society for the Study of Labour History and its journal, Labour History, which marked the field's arrival as university research. Describes the growing influence of the New Left, Marxism, women's history, and awareness of racism. Concludes with an analysis of research trends and that labour historians are influencing the writing of Australian national history.

Pêche et coopération au Québec - Gauthier, Hervé (Labour / Le Travail, 1983)
This article reviews the book, "Pêche et coopération au Québec," by Paul Larocque.

Borodin: Stalin's Man in China - Gewurtz, Margo S. (Labour / Le Travail, 1983)
This article reviews the book, "Borodin: Stalin's Man in China," by Dan N. Jacobs.

The Landrum-Griffin Act and Union Democracy - Glaberman, Martin (Labour / Le Travail, 1983)
This article reviews the book, "The Landrum-Griffin Act and Union Democracy," by Doris B. McLaughlin and Anita L.W. Schoomaker.

Workers, Bosses, and Bureaucrats - Glaberman, Martin (Labour / Le Travail, 1983)
This article reviews the book, "Workers, Bosses, and Bureaucrats," by Tom Kerry.

Clifford Odets: American Playwright, The Years from 1906-1940 - Goldie, Terry (Labour / Le Travail, 1983)
This article reviews the book, "Clifford Odets: American Playwright, The Years from 1906-1940," by Margaret Brenman-Gibson.

La vie studieuse et obstinée de Denis-Benjamin Viger (1774-1861) - Greer, Allan (Labour / Le Travail, 1983)
This article reviews the book, "La vie studieuse et obstinée de Denis-Benjamin Viger (1774-1861)," by Gérard Parizeau.

1st, 2nd, 3rd Annual Agricultural History of Ontario Seminar Proceedings 1976, 1977, 1978 - Griezic, F. J. K. (Foster Julian Kenneth) (Labour / Le Travail, 1983)
This article reviews the book, "1st, 2nd, 3rd Annual Agricultural History of Ontario Seminar Proceedings 1976, 1977, 1978," by T.A. Crowley, éd.

Canada: A History in Photographs - Heron, Craig (Labour / Le Travail, 1983)
This article reviews the book, "Canada: A History in Photographs," by Roger Hall and Gordon Dodds.

Social Science Monograph Series - Hornosty, Jennie M. (Labour / Le Travail, 1983)
This article reviews the book, "Social Science Monograph Series," by Robert Chanteloup, ed.

Making America Work: Productivity and Responsibility - Hunnius, Gerry (Labour / Le Travail, 1983)
This article reviews the book, "Making America Work: Productivity and Responsibility," by James O'Toole.

Council Communism - Huxley, Christopher (Labour / Le Travail, 1983)
The article reviews and comments on "Pannekoek and Garter's Marxism," edited by D.A. Smart, "Anti-Bolshevik Communism," by Paul Mattick, and "Marxism and Politics," by Ralph Miliband.

Puritan Boston and Quaker Philadelphia: Two Protestant Ethics and the Spirit of Class Authority and Leadership - Ingham, John N. (Labour / Le Travail, 1983)
This article reviews the book, "Puritan Boston and Quaker Philadelphia: Two Protestant Ethics and the Spirit of Class Authority and Leadership," by E. Digby Baltzell.

How to Fight for What's Right: The Citizen's Guide to Public Interest Law - Johnston, Keith (Labour / Le Travail, 1983)
This article reviews the book, "How to Fight for What's Right: The Citizen's Guide to Public Interest Law," by John Swaigen.

Labour in Nicaragua, 1983 - Judson, Fred (Labour / Le Travail, 1983)
Presents an interview with Francisco Gonzalez, Secretary of International Relations for the Central Sandinista de Trabajadores (Sandinista Trade Union Confederation), on July 9, 1983, in Managua, Nicaragua. Discusses labour organizations that support the Sandinista government, including with worker militias, in its battle against the US-backed contras, labour legal code reform, and labour education in the workplace and school.

The San Francisco Irish 1848-1880 - Kearns, William A. (Labour / Le Travail, 1983)
This article reviews the book, "The San Francisco Irish 1848-1880," by R.A. Burchell.

Prison and Plantation: Crime, Justice and Authority in Massachusetts and South Carolina, 1767-1878 - Knalfa, Louis A. (Labour / Le Travail, 1983)
This article reviews the book, "Prison and Plantation: Crime, Justice and Authority in Massachusetts and South Carolina, 1767-1878," by Michael Stephen Hindus.

The Sociology of Virtue: The Political and Social Theories of Georges Sorel - Kornberg, Jacques (Labour / Le Travail, 1983)
This article reviews the book, "The Sociology of Virtue: The Political and Social Theories of Georges Sorel," by John Stanley.

The International Working-Class Movement: Problems of History and Theory, Volume I, The Origins of the Proletariat and Its Evolution as a Revolutionary Class - Leadbeater, David (Labour / Le Travail, 1983)
This article reviews the book, "The International Working-Class Movement: Problems of History and Theory, Volume I, The Origins of the Proletariat and Its Evolution as a Revolutionary Class," by the Institute of the International Working-Class Movement, USSR Academy of Sciences, with an introduction by B.W. Ponomarev.

From Home to Office: U.S. Women at Work, 1870-1930 - Lowe, Graham S. (Labour / Le Travail, 1983)
This article reviews the book, "From Home to Office: U.S. Women at Work, 1870-1930," by Elyce J. Rotella.

Homemakers: The Forgotten Workers - Luxton, Meg (Labour / Le Travail, 1983)
This article reviews the book, "Homemakers: The Forgotten Workers," by Rae André.

The 'Crisis' and the 'Crash': Soviet Studies of the West (1917-1939) - MacDougall, Brian (Labour / Le Travail, 1983)
This article reviews the book, "The 'Crisis' and the 'Crash': Soviet Studies of the West (1917-1939)," by Richard B. Day.

Medicine in Canadian Society: Historical Perspectives - MacDougall, Heather A. (Labour / Le Travail, 1983)
This article reviews the book, "Medicine in Canadian Society: Historical Perspectives," by S.E.D. Shorn, ed.

A People and a Proletariat - Mackey, Terry (Labour / Le Travail, 1983)
This article reviews the book, "A People and a Proletariat," edited by David Smith.

Reading Capital Politically; A Guide to Marx's Capital; Value: The Representation of Labour in Capitalism - MacLean, Brian (Labour / Le Travail, 1983)
This article reviews three books: "Reading Capital Politically," by Harry Cleaver, "A Guide to Marx's Capital," by Michael Eldred and Mike Roth, and "Value: The Representation of Labour in Capitalism." edited by Diane Elson.

Frontiers of Change: Early Industrialism in America - McCalla, Douglas (Labour / Le Travail, 1983)
This article reviews the book, "Frontiers of Change: Early Industrialism in America," by Thomas C. Cochran.

Reluctant Feminists in German Social Democracy, 1885-1917 - McDonald, Lynn (Labour / Le Travail, 1983)
This article reviews the book, "Reluctant Feminists in German Social Democracy, 1885-1917," by Jean H. Quataert.

The Response to Prostitution in the Progressive Era - McGinnis, Janice Dickin (Labour / Le Travail, 1983)
This article reviews the book, "The Response to Prostitution in the Progressive Era," by Mark Thomas Connelly.

Stalin's Successors: Leadership. Stability and Change in the Soviet Union - McGrath, William (Labour / Le Travail, 1983)
This article reviews the book, "Stalin's Successors: Leadership. Stability and Change in the Soviet Union," by Seweryn Bialer.

John Ludlow: The Autobiography of Christian Socialist; Edward Carpenter. 1844-1928: Prophet of Human Fellowship - McLaren, Angus (Labour / Le Travail, 1983)
This article reviews two books: "John Ludlow: The Autobiography of Christian Socialist," edited by A.D. Murray, and " Edward Carpenter, 1844-1928: Prophet of Human Fellowship." by Chushichi Tsuzuki.

Rereading Capital - McNally, David (Labour / Le Travail, 1983)
This article reviews the book, "Rereading Capital," by Ben Fine and Laurence Harris.

Walter Lippmann and the American Century - McNaught, Kenneth (Labour / Le Travail, 1983)
This article reviews the book, "Walter Lippmann and the American Century," by Ronald Steel.

Footballers and Businessmen: The Origins of Professional Soccer in England - Metcalfe, Alan (Labour / Le Travail, 1983)
This article reviews the book: "Footballers and Businessmen: The Origins of Professional Soccer in England," by Steven Tischler.

European Resistance Movements, 1939-1945: A Complete History - Mitchell, Harvey (Labour / Le Travail, 1983)
This article reviews the book, "European Resistance Movements, 1939-1945: A Complete History," by Jorgen Haeslrup.

Making Sense of Self: Medical Advice Literature in Late Nineteenth-Century America - Mitchinson, Wendy (Labour / Le Travail, 1983)
This article reviews the book, "Making Sense of Self: Medical Advice Literature in Late Nineteenth-Century America," by Anita Clair Fellman and Michael Fellman.

The Shaping of Sudbury: A Labour View - Morrison, Jean (Labour / Le Travail, 1983)
This article reviews the book, "The Shaping of Sudbury: A Labour View," by Jim Tester.

Civilizing the West: The Gaults and the Development of Western Canada - Muise, D. A. (Labour / Le Travail, 1983)
This article reviews the book, "Civilizing the West: The Gaults and the Development of Western Canada," by A.A. den Otter.

L'action politique partisane à la FTQ (1957-1976) - Munn, Edwidge (Labour / Le Travail, 1983)
L'action politique partisane a été et demeure une des grandes préoccupations de la FTQ. À travers le cheminement idéologique et politique de la Fédération se dessine une constante: le dessein de créer un parti de la classe ouvrière. Pourtant, cet idéal controversé, source de division au sein des syndicalistes, n'arrive pas à s'affirmer concrètement. Pour faire triompher ses vues sociales et économiques, la FTQ s'engage plutôt dans une participation politique consistant à appuyer les partis dont certaines lignes directrices recoupent les revendications ouvrières. Après avoir investi un espoir illusoire dans le NPD et tenté quelques expériences provinciales peu concluantes, la FTQ pense voir dans le Parti Québécois en 1976, l'instrument par lequel elle parviendra à ses fins politiques. Notre étude analyse et dresse le bilan de ces différentes démarches et alliances.

A History of Retirement: The Meaning and Function of an American Institution, 1885-1978 - Myles, John (Labour / Le Travail, 1983)
This article reviews the book, "A History of Retirement: The Meaning and Function of an American Institution. 1885-1978," by William Graebner.

Alley Life in Washington: Family, Community. Religion, and Folklife in the City, 1850-1970 - Narváez, Peter (Labour / Le Travail, 1983)
This article reviews the book, "Alley Life in Washington: Family, Community. Religion, and Folklife in the City, 1850-1970," by James Borchert.

Culture, Communication and Dependency: The Tradition of H.A. Innis - Naylor, R. T. (Robin Thomas) (Labour / Le Travail, 1983)
This article reviews the book, "Culture, Communication and Dependency: The Tradition of H.A. Innis," edited by by William H. Melody, Liora Salter, and Paul Heyer.

Sandino - North, Liisa (Labour / Le Travail, 1983)
This article reviews the book, "Sandino," by Gregorio Selser.

Social Impact Assessment in Small Communities - Overton, D. J. B. (Labour / Le Travail, 1983)
This article reviews the book, "Social Impact Assessment in Small Communities," by RoyT. Bowles.

An Ordered Love: Sex Roles and Sexuality in Victorian Utopias–The Shakers, the Mormons, and the Oneida Community - Parr, Joy (Labour / Le Travail, 1983)
The article reviews the book, "An Ordered Love: Sex Roles and Sexuality in Victorian Utopias–The Shakers, the Mormons, and the Oneida Community," by Louis J. Kern.

The New Deal and American Tribalism: The Administration of the Indian Reorganization Act, 1934 -45 - Pastore, R.T. (Labour / Le Travail, 1983)
This article reviews the book, "The New Deal and American Tribalism: The Administration of the Indian Reorganization Act, 1934 -45," by Graham D. Taylor.

Native Land Claims: For a Just Settlement - Patterson, Lisa (Labour / Le Travail, 1983)
This article reviews the book, "Native Land Claims; For a Just Settlement," by Ben Swankey.

The French Canadian Idea of Confederation: 1864-1900 - Perin, Roberto (Labour / Le Travail, 1983)
This article reviews the book, "The French Canadian Idea of Confederation: 1864-1900," by Arthur Silver.

Industrialization, Urbanization, and Workers' Culture: The "New" Social History and the German Proletariat in the Nineteenth Century - Peterson, Larry (Labour / Le Travail, 1983)
The article reviews and comments on "The Formation of a Modern Labor Force. Upper Silesia, 1865-1914," by Lawrence Schofer, "Town in the Ruhr. A Social History of Bochum, 1860-1914," by David F. Crew, "Berliner Arbeiterviertel 1800-1918," by Horant Fassbinder, with a contribution by Ingrid Krau,"Massenwohnungsbau in Hamburg. Materialien zur Entstehung und Verdnderung Hamburger Arbeiterwohnungen und -siedlungen 1800-1967," by Hans-Jürgen Nörnberg and Dirk Schubert, "Fabrik, Familie, Feierabend. Beitrdge zur Sozialgeschichte des Ailtags im Industhezeitalter," by Jürgen Reulecke and Wolfhard Weber, "Arbeitergeschichte und Arbeiterbewegung. Industriearbeit und Organisationsverhalten im 19. und friihen 20. Jahrhundertm" by Wilhelm Heinz Schröder, "Die badische Sozialdemokratie 1890 bis 1914. Zum Zusam-menhang von Bildung und Organisation," by Konrad Elsasser, "Zur Konstituierung des Proletariats als Klasse- Strukturunter-suchung iiber das Leipziger Proletariat wdhrend der industriellen Revolution," by Hartmut Zwahr, "Sozialgeschichte der Bergarbeiterschaft an der Ruhr im 19. Jahrhundert," by Klaus Tenfelde, and "Social Democracy and Society. Working-class Radicalism in Dusseldorf, 1890-1920," by Mary Nolan.

Beyond the Monetarists: Post Keynesian Alternatives to Rampant Inflation, Low Growth and High Unemployment - Phillips, Paul (Labour / Le Travail, 1983)
This article reviews the book, "Beyond the Monetarists: Post Keynesian Alternatives to Rampant Inflation, Low Growth and High Unemployment," by David Crane, éd.

Dorothea Lange and the Documentary Tradition - Pierson, Stuart (Labour / Le Travail, 1983)
This article reviews the book, "Dorothea Lange and the Documentary Tradition," by Karin Becker Ohrn.

Subject Women. Where Women Stand Today —Politically, Economically, Socially, Emotionally - Roberts, Barbara (Labour / Le Travail, 1983)
This article reviews the book, "Subject Women. Where Women Stand Today —Politically, Economically, Socially, Emotionally," by Ann Oakley.

Black Scandal: America and the Liberian Labor Crisis, 1929-1936 - Roberts, Richard (Labour / Le Travail, 1983)
This article reviews the book, "Black Scandal: America and the Liberian Labor Crisis, 1929-1936," by I.K. Sundiata.

Strike in the Single Enterprise Community: Flin Flon, Manitoba - 1934 - Robson, Robert S. (Labour / Le Travail, 1983)
The 1934 Flin Flon Strike occurred largely as a reaction to the single enterprise nature of the community. The confrontation centred on the dominant position of the Hudson Bay Mining and Smelting Company Ltd. (HBM&S) within the community. The struggle featured the striving for legitimacy of the Mine Workers' Union of Canada (MWUC) and a Company orchestrated, anti-communist crusade. In the end the communist bogey prevailed and the workers' organization was defeated.

The Scope of Faculty Collective Bargaining: An Analysis of Faculty Union Agreements at Four-Year Institutions of Higher Education - Rodger, R.S. (Labour / Le Travail, 1983)
This article reviews the book, "The Scope of Faculty Collective Bargaining: An Analysis of Faculty Union Agreements at Four-Year Institutions of Higher Education," by R.L. Johnston.

In The Rapids of Revolution: Essays. Articles, and Letters. 1902-23 - Rowe, Andy (Labour / Le Travail, 1983)
This article reviews the book: "In The Rapids of Revolution: Essays. Articles, and Letters. 1902-23," by John MacLean, edited by Nan Milton.

Organized Workers and Socialist Politics in Interwar Japan - Schonberger, Howard (Labour / Le Travail, 1983)
This article reviews the book, "Organized Workers and Socialist Politics in Interwar Japan," by Stephen S. Large.

English America and the Restoration Monarchy of Charles II. Transatlantic Politics, Commerce, and Kinship - Sheps, Arthur (Labour / Le Travail, 1983)
This article reviews the book, "English America and the Restoration Monarchy of Charles II. Transatlantic Politics, Commerce, and Kinship," by J.M. Sosin.

Ideology and Popular Protest - Sinclair, Peter R. (Labour / Le Travail, 1983)
This article reviews the book, "Ideology and Popular Protest," by George Rudé.

European Labour Protest, 1848-1939 - Stearns, Peter N. (Labour / Le Travail, 1983)
This article reviews the book, "European Labour Protest, 1848-1939," by Dick Geary.

Diary of a Strike - Steedman, Mercedes (Labour / Le Travail, 1983)
This article reviews the book, "Diary of a Strike," 2nd edition, by Bernard Karsh.

Unionization Versus Corporate Welfare: The "Dofasco Way" - Storey, Robert (Labour / Le Travail, 1983)
This article examines the contest between the United Steelworkers of America and management at Dominion Foundries and Steel (Dofasco) for the loyalty of Dofasco workers. Situated in the 1930s and 1940s during the rise and consolidation of industrial unionism in Canada, the article traces the development at Dofasco of a corporate welfare, human relations approach to management that effectively challenged and ultimately defeated the drive for unionization. At the same time Dofasco pursued a consistent and oftentimes ruthless policy of dismissing union organizers and activists from within its workforce. Both strategies combined to produce what this paper terms the "Dofasco Way." The centrepiece of the "Dofasco Way" was the successful operation of a profit-sharing Fund. For only the profit-sharing Fund brought together both elements of the "Dofasco Way": loyalty and fear among the workers. Loyalty was created because the Fund provided security. Fear was created through threats to terminate the Fund should the company ever be organized. In the end, however, it was the programmes designed to produce loyalty that led to the Dofasco workers' rejection of unionism.

Girls, Wives, Factory Lives - Synge, Jane (Labour / Le Travail, 1983)
This article reviews the book, "Girls, Wives, Factory Lives," by Anna Pollert.

The Syndicalist Tradition and Italian Fascism - Tilly, Louise A. (Labour / Le Travail, 1983)
This article reviews the book, "The Syndicalist Tradition and Italian Fascism," by David D. Roberts.

A Class Against Itself: Power in the Nationalisation of the British Steel Industry - Tupper, Allan (Labour / Le Travail, 1983)
This article reviews the book, "Class Against Itself: Power in the Nationalisation of the British Steel Industry," by Doug McEachern.

A History of the Guyanese Working People, 1881-1905 - Turner, Mary (Labour / Le Travail, 1983)
This article reviews the book, "A History of the Guyanese Working People, 1881-1905," by Walter Rodney.

The Future of North America - Vaillancourt, Pauline (Labour / Le Travail, 1983)
This article reviews the book, "The Future of North America," edited by Elliot Feldman and Neil Nevitte.

Les cordonniers, artisans du cuir - Vennat, Pierre J. G. (Labour / Le Travail, 1983)
This article reviews the book, "Les cordonniers, artisans du cuir," by M.-A. Thivierge et N. Thivierge.

The Structured [Crowd]: Essays in English Social History - Waters, Mavis (Labour / Le Travail, 1983)
This article reviews the book, "The Structured [Crowd]: Essays in English Social History," by Harold Perkins.

The Welfare State and Canadian Federalism - Williams, Rick (Labour / Le Travail, 1983)
This article reviews the book, "The Welfare State and Canadian Federalism," by Keith G. Banting.

Capitalism: State Formation and Marxist Theory - Wylie, Robin (Labour / Le Travail, 1983)
This article reviews the book, "Capitalism: State Formation and Marxist Theory," edited by Philip Corrigan.

Plaidoyer pour le Front commun - Denis, Roch (Conjoncture politique au Québec, 1983)
Catalogue CUBIQ: https://bibliotheque.cecile-rouleau.gouv.qc.ca/notice?id=p%3A%3Ausmarcdef_0000149706&locale=fr

Abstracts = Résumés [v.11, Spring 1983] (Labour / Le Travail, 1983)

Abstracts = Résumés [v.12, Fall 1983] (Labour / Le Travail, 1983)
English/French abstracts of articles in the issue.

Index — volume 38 — 1983 (Relations Industrielles / Industrial Relations, 1983)

Liste des appréciateurs 1983 / 1983 List of Referees (Relations Industrielles / Industrial Relations, 1983)

Livres reçus / Books Received (Relations Industrielles / Industrial Relations, 1983)

Livres reçus / Books Received (Relations Industrielles / Industrial Relations, 1983)

Livres reçus / Books Received (Relations Industrielles / Industrial Relations, 1983)

Livres reçus / Books Received (Relations Industrielles / Industrial Relations, 1983)

Publications récentes / Recent Publications (Relations Industrielles / Industrial Relations, 1983)

Publications récentes / Recent Publications (Relations Industrielles / Industrial Relations, 1983)

Publications récentes / Recent Publications (Relations Industrielles / Industrial Relations, 1983)

Publications récentes / Recent Publications (Relations Industrielles / Industrial Relations, 1983)

Competing Paradigms in Industrial Relations - Adams, Roy J. (Relations Industrielles / Industrial Relations, 1983)
Despite the statute which the field of industrial relations has achieved, many essential issues regarding its nature and purpose continue to be controversial. There has emerged no universally accepted definition of the term industrial relations. The author at-tempts to demonstrate that the failure is the result of underlying conceptual structure of the field.

Organizational Commitment: Testing Two Theories - Amernic, J. H.; Aranya, N. (Relations Industrielles / Industrial Relations, 1983)
A study of organizational commitment of professional accountants who have the chartered accountancy designation, in various occupational settings in Canada, with reference to two alternative theories of organizational commitment.

Canadian Capitalism, A Study of Power in the Canadian Business Establishment - Armstrong, Christopher (Labour / Le Travail, 1983)
This article reviews the book, "Canadian Capitalism, A Study of Power in the Canadian Business Establishment," by Jorge Niosi.

The Reshaping of the National Labor Relations Board : National Labor Policy in Transition 1937-1947 - Babcock, Robert H. (Relations Industrielles / Industrial Relations, 1983)
This article reviews the book, "The Reshaping of the National Labor Relations Board : National Labor Policy in Transition 1937-1947," by James A. Gross.

Code du travail du Québec - Bachand, Gilles (Relations Industrielles / Industrial Relations, 1983)
This article reviews the book, "Code du travail du Québec," by Philip Cutler.

La grève de Lachute (1947) - Baillargeon, Denyse (Revue d'histoire de l'Amérique française, 1983)
Un article de la revue Revue d'histoire de l'Amérique française, diffusée par la plateforme Érudit.

The Miners and the Mediator: The 1906 Lethbridge Strike and Mackenzie King - Baker, William M. (Labour / Le Travail, 1983)
The attitude of United Mine Workers of America representatives towards Mackenzie King at the beginning of his mediation of the Lethbridge coal-miners' strike of 1906 was negative. At the end their opinion of him was positive. A detailed examination of the mediation process reveals that this changed outlook was a consequence of the fact that King's intervention had resulted in important gains for the strikers. These improvements had been facilitated by King but since his goal was to end the strike, specific conditions of work for Lethbridge miners were, in his mind, a means to an end rather than the end itself. Thus, in a real sense union representatives had won these gains through their tenacious and reasonably skillful "negotiations" with King himself. In short, on the whole the interplay between the mediator and union spokesmen was beneficial for Lethbridge miners.

Troubled Worker Militancy: Challenges Confronting Western Industrial Relations - Barkin, Solomon (Relations Industrielles / Industrial Relations, 1983)
This paper presents some thoughts on the development of Western industrial relations Systems since the postwar years and dwells on the questions the unions are now facing.

International Labour Conventions and Recommandations - Barré, Alain (Relations Industrielles / Industrial Relations, 1983)
This article reviews the book, "International Labour Conventions and Recommandations," by the International Labour Organization.

Décisions rendues par le Conseil canadien des relations du travail - Beaulieu, Luc (Relations Industrielles / Industrial Relations, 1983)

Statutory Recognition Provisions in Britain, 1976-1980 - Beaumont, P. B. (Relations Industrielles / Industrial Relations, 1983)
This paper assesses the extent to which the union movement in Great Britain was able to realise in practice the potential advantages of the statutory recognition provisions.

The Social Organization of Industrial Conflict : Control and Resistance in the Workplace - Bélanger, Jacques (Relations Industrielles / Industrial Relations, 1983)
This article reviews the book, "The Social Organization of Industrial Conflict: Control and Resistance in the Workplace," by P.K. Edwards & Hugh Scullion.

Human Resources Management. An Information Systems Approach - Bélanger, Laurent (Relations Industrielles / Industrial Relations, 1983)
This article reviews the book, "Human Resources Management. An Information Systems Approach," by Wayne C. Cascio & Elias M. Award.

Le changement planifié - Bélanger, Laurent (Relations Industrielles / Industrial Relations, 1983)
This article reviews the book, "Le changement planifié," by Pierre Collerette & Gilles Delisle.

Managing Individual and Group Behavior in Organizations - Bélanger, Laurent (Relations Industrielles / Industrial Relations, 1983)
This article reviews the book, "Managing Individual and Group Behavior in Organizations," by Daniel C. Feldman & Hugh J. Arnold.

Productivité et qualité de vie au travail - Bélanger, Laurent (Relations Industrielles / Industrial Relations, 1983)
This article reviews the book, "Productivité et qualité de vie au travail," by Maurice Lemelin & Jeannine McNeil.

L’extension juridique des conventions collectives au Québec : une approche comparative - Bernier, Jean (Relations Industrielles / Industrial Relations, 1983)
Après avoir rappelé les nombreuses études que le gouvernement du Québec a fait réaliser depuis une vingtaine d'années sur les régimes européens d'extension juridique des conventions collectives, l'auteur recourt à l'approche comparative pour tenter de dégager un certain nombre de questions susceptibles défavoriser un réexamen du système québécois d'extension juridique.

The Five Dollar Day: Labour Management and Social Control in the Ford Motor Company, 1908-1921 - Bloomfield, G.T. (Labour / Le Travail, 1983)
This article reviews the book, "The Five Dollar Day: Labour Management and Social Control in the Ford Motor Company, 1908-1921," by Stephen Meyer III.

Discrimination and the Law in Canada - Blouin, Rodrigue (Relations Industrielles / Industrial Relations, 1983)
This article reviews the book, "Discrimination and the Law in Canada," by Walter Surman Tanopolsky.

Les mesures disciplinaires : étude jurisprudentielle et doctrinale - Blouin, Rodrigue (Relations Industrielles / Industrial Relations, 1983)
This article reviews the book, "Les mesures disciplinaires : étude jurisprudentielle et doctrinale," by C. D’Aoust, L. Leclerc & G. Trudeau.

Work and Revolution in France: The Language of Labor from the Old Regime to 1848 - Borghese, Arthur (Labour / Le Travail, 1983)
This article reviews the book, "Work and Revolution in France: The Language of Labor from the Old Regime to 1848," by William H. Sewell, Jr.

Qualité de vie au travail : anti-stress et créativité - Boulard, René (Relations Industrielles / Industrial Relations, 1983)
This article reviews the book, "Qualité de vie au travail : anti-stress et créativité," by Pierre A. Turcotte.

Work Hazards and Industrial Conflicts - Boulard, René (Relations Industrielles / Industrial Relations, 1983)
This article reviews the book, "Work Hazards and Industrial Conflicts," by Carl Gersuny.

La loi sur la santé et la sécurité du travail et les conventions collectives - Boulard, René; Marchand, Michel (Relations Industrielles / Industrial Relations, 1983)
La Loi sur la santé et la sécurité du travail, adoptée en décembre 1979 par la législature québécoise, a-t-elle eu un impact sur les clauses de conventions collectives? Les auteurs examinent la situation dans les secteurs prioritaires de la Commission de la santé et de la sécurité du travail.

The Indian, the Métis and the fur trade class, sexism and racism in the transition from “Communism” to Capitalism - Bourgeault, Ron G. (Studies in Political Economy, 1983)
The object of this paper is to argue that the fur trade of the Hudson Bay basin, in what is now northern Canada, initially transformed Indian labour into that of a peasantry caught in the web of feudal relations of production. The paper will also show the nature of Indian women's subjugation, a subjugation undertaken to establish the fur trade. Class, racial and sexist divisions came to be imposed upon the indigenous Indian population through colonial relations based upon a particular form of exploitation. –From author's introduction.

Farm to Factory: Women's Letters, 1830-1860 - Brandt, Gail Cuthbert (Labour / Le Travail, 1983)
This article reviews the book, "Farm to Factory. Women's Letters, 1830-1860," edited by Thomas Dublin.

The ACLU and the Wagner Act: An Inquiry into the Depression-Era Crisis of American Liberalism - Brody, David (Labour / Le Travail, 1983)
This article reviews the book, "The ACLU and the Wagner Act: An Inquiry into the Depression-Era Crisis of American Liberalism," by Cletus E. Daniel.

Procédures de règlement pacifique des conflits collectifs en France - Caire, Guy (Relations Industrielles / Industrial Relations, 1983)
L'auteur décrit et interprète le particularisme de la procédure d'arbitrage des conflits collectifs du travail en France qui offre l'image contradictoire de l'échec des modalités officielles de règlement et de la vertu des procédures informelles.

An International Comparison of the Volatility of Strike Behavior - Cameron, Samuel (Relations Industrielles / Industrial Relations, 1983)
This paper develops a synthetic mode! of the strike process which suggests the use of volatility as the measure of severity rather than levels or regression intercepts.

An Outlook on Labour Relations in Canada - Carrothers, A. W.R. (Relations Industrielles / Industrial Relations, 1983)
The object of this paper is to examine the conditions of labour relations in Canada, with a view to trying to assess what is likely to happen in the next few years; and to try to identify what review of policies and practices might be considered in an effort to ameliorate the present unhappy condition of Canadian labour relations.

Gentlemen Emigrants: From the British Public Schools to the Canadian Frontier - Cherwinski, W. J. C. (Walter Joseph Carl) (Labour / Le Travail, 1983)
This article reviews the book, "Gentlemen Emigrants: From the British Public Schools to the Canadian Frontier," by Patrick A. Dunae.

Gestion de la rémunération : Politiques et pratiques efficaces et équitables - Chouinard, Jacques (Relations Industrielles / Industrial Relations, 1983)
This article reviews the book, "Gestion de la rémunération : Politiques et pratiques efficaces et équitables," by Roland Thériault & Gaétan Morin, edited.

Annual general meeting [1983] - Committee On Canadian Labour History = Comité d'histoire de travailleurs Canadiens (Labour / Le Travail, 1983)
Minutes of the annual meeting of the Committee held on June 8, 1983.

Women's Oppression Today: Problems in Marxist Feminist Analysis - Connelly, M. Patricia (Labour / Le Travail, 1983)
This article reviews the book, "Women's Oppression Today: Problems in Marxist Feminist Analysis," by Michelle Barrett.

"Man Over Money:" The Southern Populist Critique of American Capitalism - Conway, J.F. (Labour / Le Travail, 1983)
This article reviews the book, "'Man Over Money:' The Southern Populist Critique of American Capitalism," by Bruce Palmer.

Women and American Socialism, 1870-1920; As Equals and As Sisters: Feminism, Unionism, and the Women's Trade Union League of New York - Conway, J.F. (Labour / Le Travail, 1983)
This article reviews two books: "Women and American Socialism, 1870-1920," by Mari Jo Buhle, and " As Equals and As Sisters: Feminism, Unionism, and the Women's Trade Union League of New York," by Nancy Schrom Dye.

International Labour Law Reports - Côté, André C. (Relations Industrielles / Industrial Relations, 1983)
This article reviews the book, "International Labour Law Reports," by Zvi H. Bar-Niv.

Rapports collectifs du travail - Côté, André C. (Relations Industrielles / Industrial Relations, 1983)
This article reviews the book, "Rapports collectifs du travail," by Fernand Morin.

The Arbitration Guide: a Case-handing Manual of Procedures and Practices in Dispute Resolutions - Côté, André C. (Relations Industrielles / Industrial Relations, 1983)
This article reviews the book, "The Arbitration Guide: a Case-handing Manual of Procedures and Practices in Dispute Resolutions," by Raymond L. Britton.

Le climat des relations du travail à Montréal et à Toronto - Cousineau, Jean-Michel; Lacroix, Robert (Relations Industrielles / Industrial Relations, 1983)
Cet article compare le climat des relations du travail des régions métropolitaines de Montréal et de Toronto pour le secteur privé de leur activité économique.

Matters of Loyalty: The Buells of Brockville, 1830-1850 - Cross, Michael S. (Labour / Le Travail, 1983)
This article reviews the book, "Matters of Loyalty: The Buells of Brockville, 1830-1850," by Ian MacPherson.

An International Comparison of Work Sharing Programs - Crowley, R.W.; Huth, E. (Relations Industrielles / Industrial Relations, 1983)
This article draws together primarily unpublished information that provides comparative information with respect to North American and Western European experiences with work sharing.

Le dispositif d’une sentence arbitrale : quelques pièges à éviter… - D’Aoust, Claude (Relations Industrielles / Industrial Relations, 1983)

Les ententes individuelles et la convention collective - D’Aoust, Claude (Relations Industrielles / Industrial Relations, 1983)

Early Industrialization and Inequality in Toronto, 1861-1899 - Darroch, A. Gordon (Labour / Le Travail, 1983)
Using samples of available assessment roll data for Toronto, this article maps patterns of inequality, by decades, over the years of early industrialization, 1861 -1899. The limits of these data and the many legal exclusions are reviewed; it is argued that assessed values best represent differences in everyday living conditions, rather than in wealth, property or income. Several ways of examining the extent of inequality are considered. As expected, inequality among households was pronounced, although several measures revealed an intriguing pattern of initial increase in inequality, 1861-1871, and subsequent, modest decline to the end of the century. An attempt to account for the pattern in terms of the aging of the city population turned up only very limited effects. Some implications of the patterns are considered for the analysis of class and household economies.

Chômage chez les jeunes : Conséquences psychologiques et sociales - Demers, Marie (Relations Industrielles / Industrial Relations, 1983)
À partir d'une revue de la littérature sur le chômage des jeunes que l'auteur a dépouillée en provenance des États-Unis, de la France, de la Grande-Bretagne et de l'Australie, celle-ci dégage les changements qui se sont opérés ainsi que les problèmes sociaux qu'entraîne ce phénomène.

Promise of Eden: The Canadian Expansionist Movement and the Idea of the West 1856-1900 - Den Otter, A. A. (Labour / Le Travail, 1983)
This article reviews the book, "Promise of Eden: The Canadian Expansionist Movement and the Idea of the West 1856-1900," by Doug Owram.

Les facteurs d’apparition du syndicalisme catholique dans l’imprimerie et les déterminants de la stratégie syndicale 1921-1945 - Desrochers, Luc (Revue d'histoire de l'Amérique française, 1983)
Un article de la revue Revue d'histoire de l'Amérique française, diffusée par la plateforme Érudit.

Organizing Dixie: Alabama Workers in the Industrial Era; Southern Workers and their Unions, 1880-1975: Selected Papers (The Second Southern Labor History Conference, 1978) - Dick, W. M. (William M.) (Labour / Le Travail, 1983)
This article reviews two books: "Organizing Dixie: Alabama Workers in the Industrial Era," by Philip Taft, and Southern Workers and their Unions,1880-1975: Selected Papers (The Second Southern Labor History Conference, 1978)," edited by Merl E. Reed, Leslie S. Hough, and Gary M. Fink.

Les relations du travail. Employeurs, personnel, syndicats, État - Dion, Gérard (Relations Industrielles / Industrial Relations, 1983)
This article reviews the book, "Les relations du travail. Employeurs, personnel, syndicats, État," by Dimitri Weiss.

Historiographie du Parti communiste canadien 1960-1982 - Dionne, Bernard (Revue d'histoire de l'Amérique française, 1983)

Repenser l’évaluation - Dionne, Pierre; Ouellet, Gilles (Relations Industrielles / Industrial Relations, 1983)
Les auteurs cherchent ici à faire le point sur l'état de la recherche en évaluation du potentiel humain.

"All That Our Hands Have Done" ; A Pictorial History of the Hamilton Workers - Dodds, Gordon (Labour / Le Travail, 1983)
This article reviews the book, "'All That Our Hands Have Done': A Pictorial History of the Hamilton Workers," compiled by Craig Heron, Shea Hoffmitz, Wayne Roberts, and Robert Storey.

L’absentéisme hospitalier au Québec : aspects culturels et socio-démographiques - Dolan, Shimon L.; Arsenault, André; Lizotte, Jean-Paul; Abenhaim, Lucien (Relations Industrielles / Industrial Relations, 1983)
Cet article porte sur certains aspects de l'absentéisme en milieu hospitalier au Québec. L'intérêt principal ici réside dans la remise en question de certaines pratiques analytiques.

Robert Lowery: Radical and Chartist - Donnelly, F. K. (Labour / Le Travail, 1983)
This article reviews the book, "Robert Lowery: Radical and Chartist," edited by Brian Harrison and Patricia Hollis.

Canadian Union Growth - Eastman, Byron (Relations Industrielles / Industrial Relations, 1983)
This paper spécifies a model of trade union membership growth in Canada. Because union growth affects and is affected by wage and price inflation, the model incoporates simultaneous équations with thèse three variables in endogeneous rôles.

The Bargaining Process and Mediation - Fisher, E. G. (Relations Industrielles / Industrial Relations, 1983)
This article reviews the book, "The Bargaining Process and Mediation," by the Education Relations Commission.

The Impact of Unanticipated Output and Consumer Prices on Wilcat Strikes - Fisher, E. G.; Percy, M. B. (Relations Industrielles / Industrial Relations, 1983)
An empirical investigation of the impact of unanticipated changes in output and consumer prices, as well as other economic and sociological variables, on midcontract or wildcat strikes, with particular reference to British Columbia's copper industry.

Old Trails and New Directions: Papers of the Third North American Fur Trade Conference - Friesen, Jean (Labour / Le Travail, 1983)
This article reviews the book, "Old Trails and New Directions: Papers of the Third North American Fur Trade Conference," edited by Carol M. Judd and Arthur J. Ray.

Lives of Their Own: Blacks. Italians, and Poles in Pittsburgh, 1900-1960 - Frisch, Michael H. (Labour / Le Travail, 1983)
This article reviews the book, "Lives of Their Own: Blacks. Italians, and Poles in Pittsburgh, 1900-1960," by John Bodnar, Roger Simon, and Michael P. Weber.

International Socialism and Australian Labour: The Left in Australia, 1919-1930 - Fry, Eric (Labour / Le Travail, 1983)
This article reviews the book, "International Socialism and Australian Labour: The Left in Australia, 1919-1930," by Frank Farrell.

Bahro Refuted: Solidarnosc and Proletarian Revolution in Eastern Europe - Gabbert, Mark (Labour / Le Travail, 1983)
The article reviews and comments on "The Polish August: The Self-Limiting Revolution," by Neal Ascherson, "The Alternative in Eastern Europe," by Rudolf Bahro, "At The Lenin Shipyard: Poland and the Rise of the Solidarity Trade Union," by Stan Persky, and "The Road to Gdansk: Poland and the U.S.S.R.," 2nd edition, by Daniel Singer.

La gestion des conflits interpersonnels en milieu universitaire - Garnier, Bernard (Relations Industrielles / Industrial Relations, 1983)
Cet article examine l'utilisation et l'efficacité des méthodes de gestion de conflit interpersonnel utilisées par les doyens d'université avec leurs directeurs de département et les professeurs de leur faculté. L'auteur discute les implications théoriques de l'étude pour la gestion des conflits ainsi que les implications pratiques pour l'administrateur.

Changements dans les législations du travail au Canada [v. 38, no. 1, 1983] - Gauvin, Michel; Lascelle, Michael; Brennan, Geoffrey (Relations Industrielles / Industrial Relations, 1983)
Le règlement, qui a un effet rétroactif au 18 février 1982, contient des directives concernant la stabilisation des traitements dans le secteur public. Il précise de quelle manière ces directives sont appliquées ceci comprenant la détermination du début de la période de contrôle. Pour la première période de contrôle qui est de 12 mois, le maximum suggéré d'augmentation est de 6% avec des variations maximales de plus 4% ou de moins 6% selon les traitements qui ont été accordés au groupe concerné par le passé et selon des circonstances spéciales telles que définies. Pour la seconde période de contrôle, qui est normalement de la même longueur, le taux maximum suggéré est de 5% avec des variations maximales de plus 4% ou de moins 5% selon le niveau d'inflation, les traitements accordés dans le passé et des circonstances spéciales. Il n'y a pas d'augmentation pour les cadres supérieurs.

Changements dans les législations du travail au Canada [v. 38, no. 2, 1983] - Gauvin, Michel; Lawrence, Jeffrey; Brennan, Geoffrey (Relations Industrielles / Industrial Relations, 1983)

Changements dans les législations du travail au Canada [v. 38, no. 3, 1983] - Gauvin, Michel; Lawrence, Jeffrey; Brennan, Geoffrey (Relations Industrielles / Industrial Relations, 1983)

Changements dans les législations du travail au Canada [v. 38, no. 4, 1983] - Gauvin, Michel; Lawrence, Jeffrey; Brennan, Geoffrey (Relations Industrielles / Industrial Relations, 1983)

L’émergence d’une scène politique : mouvement ouvrier et mouvements de réforme urbaine à Montréal au tournant du siècle — Essai d’interprétation - Germain, Annick (Revue d'histoire de l'Amérique française, 1983)

Harry Douglas Woods, 1907-1983 - Goldenberg, Shirley B.; Hébert, Gérard (Relations Industrielles / Industrial Relations, 1983)

The Unemployment of Youth: The Importance of Education for their Adjustment in the Canadian Labour Market - Gunderson, Morley (Relations Industrielles / Industrial Relations, 1983)
This article reviews the book, "The Unemployment of Youth: The Importance of Education for their Adjustment in the Canadian Labour Market," by Joya Sen.

British Labor and the American Civil War - Harrison, Royden (Labour / Le Travail, 1983)
This article reviews the book, "British Labor and the American Civil War," by Philip S. Foner.

Embattled Shadows: A History of Canadian Cinema; John Grierson: A Documentary Biography - Heron, Craig (Labour / Le Travail, 1983)
This article reviews two books: "Embattled Shadows: A History of Canadian Cinema," by Peter Morris, and "John Grierson: A Documentary Biography," by Forsyth Hardy.

Les origines des travailleurs de l’Alcan au Saguenay, 1925-1939 - Igartua, José; de Fréminville, Marine (Revue d'histoire de l'Amérique française, 1983)
Un article de la revue Revue d'histoire de l'Amérique française, diffusée par la plateforme Érudit.

Micro-electronics Technology and Industrial Relations - Jain, Harish C. (Relations Industrielles / Industrial Relations, 1983)

Urban Complex of an Industrial City - Jain, Hem C. (Relations Industrielles / Industrial Relations, 1983)
This article reviews the book, "Urban Complex of an Industrial City," by Jugendra Sahai.

Bitter Harvest, a History of Californian Farmworkers, 1870-1941 - Jamieson, Stuart Marshall (Labour / Le Travail, 1983)
The article reviews the book, "Bitter Harvest, a History of Californian Farmworkers, 1870-1941," by Cletus E. Daniel.

La réduction de la durée du travail est-elle créatrice d’emploi? - Jolivet, Thierry (Relations Industrielles / Industrial Relations, 1983)

Perfecting the Administrative Solution to Labour Disputes: Postscript - Joseph, P. A. (Relations Industrielles / Industrial Relations, 1983)
The judges lack the intimate knowledge of the very dynamic process of industrial relations and collective bargaining. For these reasons...the new labour code has removed the court's jurisdiction over labour disputes...The new law seeks an administrative rather than a judicial solution to labour disputes

Perfecting the Administrative Solution to Labour Disputes. British Columbia Experiment - Joseph, Philip A. (Relations Industrielles / Industrial Relations, 1983)
An analysis of the unique nature of the administrative solution to labour disputes in British Columbia experience, with particular reference to section 33 of the Labour Code.

Pluralità : Italia ed Europa nei conflitti industriali - Joubert, P. (Relations Industrielles / Industrial Relations, 1983)
This article reviews the book, "Pluralità : Italia ed Europa nei conflitti industriali," by Umberto Romagnoli, Dimitri Weiss et al.

Politica, partidos y sindicatos en la empresa ; El poder sindical en Espana - Joubert, P. (Relations Industrielles / Industrial Relations, 1983)
This article reviews the book, "Politica, partidos y sindicatos en la empresa," by Dimitri Weiss. This article reviews the book, "El poder sindical en Espana," by J.A. Sagardoy Bengoechea & Daved Leon Blanco.

Possono migliorare le relzioni industriali in Italia? - Joubert, P. (Relations Industrielles / Industrial Relations, 1983)
This article reviews the book, "Possono migliorare le relzioni industriali in Italia?," by Gino Giugni, Luigi Mengoni, Felice Mortillaro & Dimitri Weiss.

Shop Stewards, Workers and Managers in Israëli Industry - Kaminka, Shlomit; Rosenstein, Eliezer (Relations Industrielles / Industrial Relations, 1983)
This paper describes and analyses the place of the shop steward committee in the constellation of relationships at the workplace and pays special attention to the relations between the shop steward committee and the workers.

Editor's Note = Note du directeur [11, Spring/Printemps 1983] - Kealey, Gregory S. (Labour / Le Travail, 1983)
Takes note of the poetry published in the issue, including an accompanying essay. Bryan Palmer will soon be contributing as the review editor. Following an SSHRCC investigation of alternative formats, the print publication of the journal will continue to have primacy over microfiche.

Editor's Note = Note du directeur [12, Fall 1983] - Kealey, Gregory S. (Labour / Le Travail, 1983)
Takes note that a previously published book review by Jacques Roulliard is being reprinted with corrections in the current issue.

" The Bonds of Unity": Some Further Reflections - Kealey, Gregory; Palmer, Bryan (Histoire sociale/Social History, 1983)
Replies to Michael Piva's "comment" on statistics regarding the proportion of the Ontairo working population who were members of the Knights of Labor. Concedes that there was an error, but argues with Piva's usage of 1891 Canadian census data and his pessimistic assessment of the Knights' impact.

Book Notes [11, Spring 1983] - Kealey, Linda; Fitting, Peter; Doucette, Laurel (Labour / Le Travail, 1983)
The article provides reviews of: Women's History Sources: A Guide to Archives and Manuscript Collections in the United States, 2 v., edited by Andrea Hinding / review by Linda Kealey – Marxism and Culture: The CPUSA and Aesthetics in the 1930s, by Lawrence H. Schwartz / review by Peter Fitting – A Bibliography of Canadian Folklore in English, compiled by Edith Fowke and Carole Henderson Carpenter / review by Laurel Doucette.

Reconcilable Differences; Grievance Arbitration of Discharge Cases; Labour Law and Industrial Relations in Canada - Langille, Brian (Labour / Le Travail, 1983)
This article reviews three books: "Reconcilable Differences," by Paul Weiler, "Grievance Arbitration of Discharge Cases," by George W. Adams, and "Labour Law and Industrial Relations in Canada," by H.W. Arthurs, D.D. Carter, and H..J. Glasbeek.

La qualité de vie au travail et l’horaire variable - Larouche, Viateur; Trudel, Johanne (Relations Industrielles / Industrial Relations, 1983)
L'objet de cette étude est de vérifier si la transformation des horaires de travail peut affecter directement la qualité de la vie au travail. Les auteurs précisent d'abord le nouveau concept de qualité de vie au travail, ils font ensuite le tour des différents types horaires alternatifs de travail et enfin analysent d'une façon particulière l'horaire variable à la lumière de quelques cas pratiques.

Décisions rendues par le Conseil canadien des relations du travail - Lavery, Daniel (Relations Industrielles / Industrial Relations, 1983)
Le Conseil fut saisi d'un conflit de distribution du travail entre syndicats rivaux engendré par l'absence de quelque mention relative à la fonction disputée dans leurs certificats d'accréditation ou conventions collectives alors que ladite fonction existait au moment de leur accréditation respective. Le Conseil a expliqué le fondement de sa juridiction en vertu des articles 158(1) et 119 du Code pour trancher de tels litiges. Il a rappelé, par ailleurs, sa politique habituelle quant au caractère approprié de l'unité et l'objectif des votes de représentation lors du dépôt, par un syndicat maraudeur, d'une requête en accréditation visant à représenter une unité dont la délimitation épouse fidèlement celle pour laquelle le syndicat en place a déjà été accrédité. Enfin, en étudiant la nature de la fonction litigieuse tel qu 'elle a évolué depuis sa création jusqu'au moment de l'audition de la présente affaire, le Conseil a déterminé que la convention collective du syndicat requérant ne s'appliquait pas à la fonction litigieuse sauf quant à certains aspects de ce travail.

Décisions rendues par le Conseil canadien des relations du travail - Lavery, Daniel (Relations Industrielles / Industrial Relations, 1983)
Le Conseil canadien des relations du travail a rendu une décision dans laquelle il a étudié la légalité de certaines clauses des protocols de retour au travail, le statut des substituts engages et promus durant la grève ainsi que la doctrine de la conversion d'une grève économique en une grève dite de pratiques déloyales. Au terme de cette decision il a déclaré l'employeur «coupable» d'avoir commis un certain nombre de pratiques déloyales et a ordonné, en conséquence, que les employés grévistes soient réintégrés, une fois la grève terminée, dans leurs fonctions antérieures ou à des postes substantiellement équivalent meme si pour cela, les substituts engagés durant la grève devaient être déplacés, transférés, retrogrades ou tout simplement congédiés par l'employeur de façon à faire place aux grévistes. Selon l'approche adoptee par le Conseil, le statut des substituts originant de l'extérieur de l'unité engages en période de grève ne saurait être que temporaire et n 'est susceptible de se transformer et de devenir permanent que lors de la survenance de certains événements. L'octroi de la permanence par l'employeur avant que ces événements ne soient survenus constitue en soi une pratique déloyale ayant pour effet de convertir la grève en une grève dite de pratiques déloyales de travail et, partant, de conférer un droit absolu à la reintegration aux grévistes dont les postes ont été comblés subséquemment à la conversion.

Décisions rendues par le Conseil canadien des relations du travail - Lavery, Daniel (Relations Industrielles / Industrial Relations, 1983)
Les effets découlant de l'octroi d'un certificat d'accréditation et l'émasculation de l'unité de négociation.

Capital and Labour in Canada 1650-1860 - Laxer, Gordon D. (Labour / Le Travail, 1983)
This article reviews the book, "Capital and Labour in Canada 1650-1860," by H. Clare Pentland.

The Canadian Labour Bibliography / La Bibliographie du mouvement ouvrier canadien [12, Fall 1983] - Leduc, Marcel; Vaisey, Douglas (Labour / Le Travail, 1983)
Compilation of recent English/French publications on Canadian labour history that emphasize the period 1800-1975. Materials pertaining to the post-1975 period may also be included, although more selectively. [See the database, Canadian Labour History, 1976-2009, published at Memorial University of Newfoundland.]

In Praise of Reform Capitalism: The Economic Ideas of O.D. Skelton - Levitt, Joseph (Labour / Le Travail, 1983)
Portrays the life and thought of Oscar Douglas Skelton (1878-1941), a liberal reformer who became Canada's top civil servant under Mackenzie King's government. Focuses on Skelton's perspectives on labour, capitalism, socialism, and Marxism.

Popular Disturbances in England, 1700-1870 - Linebaugh, Peter (Labour / Le Travail, 1983)
This article reviews the book, "Popular Disturbances in England, 1700-1870," by John Stevenson.

The Renaissance of Homeworking in Developed Economies - Lipsig-Mummé, Carla (Relations Industrielles / Industrial Relations, 1983)
The purpose of this paper is to offer an analysis and overview of the causes and implications of the renaissance of homeworking in many industries in Western Europe, North America and Australia since the 1960's.

Canadian Papers in Rural History, Vol. III - Little, J.i. (Labour / Le Travail, 1983)
This article reviews the book, "Canadian Papers in Rural History, Vol. III," edited by Donald H. Akenson.

Women for Hire: A Study of the Female Office Worker - Lowe, Graham S. (Labour / Le Travail, 1983)
This article reviews the book, "Women for Hire: A Study of the Female Office Worker," by Fiona McNally.

Women and Household Labor; Working Women and Families; Urban Survival: The World of Working Class Women - Luxton, Meg (Labour / Le Travail, 1983)
This article reviews three books: "Women and Household Labor," edited by Sarah Fenstermaker Berk, "Working Women and Families," edited by Karen Wolk Feinstein, and "Urban Survival: The World of Working Class Women," by Ruth Seidel.

Sharing the Work: An Analysis of the Issues in Worksharing and Jobsharing - Macdonald, W. Stephen (Labour / Le Travail, 1983)
This article reviews the book, "Sharing the Work: An Analysis of the Issues in Worksharing and Jobsharing," by Noah M. Meltz, Frank Reid, and Gerald S. Swartz.

The Rise and Fall of the Toronto Typographical Union 1832-1972: A Case Study of Foreign Domination - Macdowell, Laurel Sefton (Labour / Le Travail, 1983)
This article reviews the book, "The Rise and Fall of the Toronto Typographical Union 1832-1972: A Case Study of Foreign Domination," by Sally F. Zerker.

The Placement Activity on the Canadian Employment Agency - Magun, Sunder (Relations Industrielles / Industrial Relations, 1983)
This paper studies three aspects of the job matching process of the Canada Employment Centres.

Trade Unions and Productivity: Conventional Estimates - Maki, Dennis R. (Relations Industrielles / Industrial Relations, 1983)
This paper discusses the issues and concepts involved hère, criticizes récent studies and suggests an agenda for future research. The author also présents some empirical results pertaining to Canadian manufacturing.

British Labour History, 1815-1914 - Malcolmson, Robert W. (Labour / Le Travail, 1983)
This article reviews the book, "British Labour History, 1815-1914," by E.H. Hunt.

Condition féminine en milieu ouvrier - Marchis-Mouren, Marie Françoise (Relations Industrielles / Industrial Relations, 1983)
This article reviews the book, "Condition féminine en milieu ouvrier," by Alain Vinet, Francine Dufresne & Lucie Vézina.

Actors and Systems. The Politics of Collective Action - Matejko, Alexander J. (Relations Industrielles / Industrial Relations, 1983)
This article reviews the book, "Actors and Systems. The Politics of Collective Action," by Michel Crozier & Erhard Friedberg.

Sociologie des conflits du travail - Matejko, Alexander J. (Relations Industrielles / Industrial Relations, 1983)
This article reviews the book, "Sociologie des conflits du travail," by Jean-Daniel Reynaud.

The Future of Work - Matejko, Alexander J. (Relations Industrielles / Industrial Relations, 1983)
This article reviews the book, "The Future of Work," by John Wilkes, edited.

The Social Organization of Industrial Conflict. Control and Resistance in the Workplace - Matejko, Alexander J. (Relations Industrielles / Industrial Relations, 1983)
This article reviews the book, "The Social Organization of Industrial Conflict. Control and Resistance in the Workplace," by P.K. Edwards & Hugh Scullion.

Workplace Democracy: An Inquiry into Employee Participation in Canadian Work Organizations - Matejko, Alexander J. (Relations Industrielles / Industrial Relations, 1983)
This article reviews the book, "Workplace Democracy: An Inquiry into Employee Participation in Canadian Work Organizations," by Donald V. Nightingale.

Workplace Democracy and Social Change - Matejko, Alexander J. (Relations Industrielles / Industrial Relations, 1983)
This article reviews the book, "Workplace Democracy and Social Change," by Frank Lindenfeld & Joice Rothschild-Whitt, edited.

Skill and the English Working Class, 1870-1914 - McGinnis, David (Labour / Le Travail, 1983)
This article reviews the book, "Skill and the English Working Class, 1870-1914," by Charles More.

The Economic Development of Canada - McInnis, R. M. (R. Marvin) (Labour / Le Travail, 1983)
The article reviews the book, "The Economic Development of Canada," by Richard Pomfret.

Strikes in the Maritimes, 1901-1914 - McKay, Ian (Acadiensis, 1983)
Recent studies have illustrated the strength and significance of working-class movements in the Maritimes during the late 19th and early 20th centuries. Other work has emphasized the organization of local and international unions and the emergence of the socialist movement in the region. A study of strikes in the Maritimes can help provide a regional context for such work, and also help correct the regional imbalance in national historiography. Strikes themselves were crucial events, and no historical interpretation of the region in this period can safely overlook them. By studying the vigorous response of the region's workers to the new political economy of the early 20th century, we can start to understand the human implications of economic change. For these reasons, it is worth our effort to describe and analyze the general pattern of strikes, often in quantitative terms. This general pattern can then be related to the region's economic structure and help broaden our understanding of the economic revolution which transformed the region from the 1880s to the 1920s. In particular, two major themes emerge from this analysis: the transformation of the labour market and the revolution in the workplace. –From author's introduction

Reasonable Notice Criteria in Common Law Wrongful Dismissal Cases - McShane, Steven L. (Relations Industrielles / Industrial Relations, 1983)
An empirical study to analyse the criteria that Canadian courts have used to determine the length of notice to award.

E. P. Thompson dans des arpents de neige : les historiens canadiens-anglais et la classe ouvrière - Morton, Desmond (Revue d'histoire de l'Amérique française, 1983)

Resources and Results in Union Rivalry: A Case Study - Mount, Joan; Siegel, Jacob P. (Relations Industrielles / Industrial Relations, 1983)
This paper shows the asymetric disequilibrium between available resources and results in the course of a union recruiting campaign in a case study of an experience of CUPE and LUSSA at Laurentian University.

Theory Z: Myths, Realities and Atlernatives - Mroczkowski, Thomasz (Relations Industrielles / Industrial Relations, 1983)
An assessment of substance and impact of Theory Z on American management in the context of alternative paths toward employee participation.

Canadian Newspapers: The Inside Story - O'Connor, Alan (Labour / Le Travail, 1983)
This article reviews the book, "Canadian Newspapers: The Inside Story," edited by Walter Stewart.

Industrial Folklore: A Critical Introduction - O'Connor, Alan (Labour / Le Travail, 1983)
The article reviews and comments on "Picking Up the Linen Threads: A Study in Industrial Folklore," by Betty Messenger, "Working Americans: Contemporary Approaches to Occupational Folklife" (special issue of Western Folklore, 37 (1978), reprinted as Smithsonian Folklife Studies Number 3), edited by Robert H. Byington, and "Land of the Millrats," by Richard M. Dorson.

"The Misery of Our Poor": Recent Studies in Development Literature - Ommer, Rosemary E. (Labour / Le Travail, 1983)
The article reviews and comments on "Centre and Periphery: Spatial Variation in Politics," edited by Jean Gottmann, "Under-Developed Europe: Studies in Core-Periphery Relations," by Dudley Seers, Bernard Schaffer, and Marja-Liisa Kiljunen, "Transnational Capitalism and National Development: New Perspectives on Dependence," edited by Jose J. Villamil, "The World-System of Capitalism: Past and Present," (volume 2 of the Political Economy of the World-System Annuals), edited by Walter L. Goldfrank, "Processes of the World-System," (volume 3 of the Political Economy of the World-System Annuals), edited by Terence K. Hopkins and Immanuel Wallerstein, and "The New International Division of Labour," by Folker Frobel, Jurgen Heinrichs, and Otto Kreye.

Timber Colony: A Historical Geography of Early Nineteenth Century New Brunswick - Ommer, Rosemary E. (Labour / Le Travail, 1983)
This article reviews the book, "Timber Colony. A Historical Geography of Early Nineteenth Century New Brunswick," by Graeme Wynn.

Canadian Bolsheviks: The Early Years of the Communist Party of Canada - Palmer, Bryan D. (Labour / Le Travail, 1983)
This article reviews the book, "Canadian Bolsheviks: The Early Years of the Communist Party of Canada," by Ian Angus.

People's History and Socialist Theory; East End Underworld: Chapters in the Life of Arthur Harding; Rothschild Buildings: Life in an East End Tenement Block, 1887-1920 - Palmer, Bryan D. (Labour / Le Travail, 1983)
This article reviews three books: "People's History and Socialist Theory," edited by Raphael Samuel, "East End Underworld: Chapters in the Life of Arthur Harding," edited by Raphael Samuel, and "Rothschild Buildings: Life in an East End Tenement Block, 1887-1920," by Jerry White.

Les relations du travail au Québec - Papale, Antimo (Labour / Le Travail, 1983)
This article reviews the books, "Les relations du travail au Québec," by Emile Bouvier, S.J.

Managers and Management in West Germany - Paquin, Michel (Relations Industrielles / Industrial Relations, 1983)
This article reviews the book, "Managers and Management in West Germany," by Peter Lawrence.

The Attitude of Trade Unions Towards Technological Changes - Peitchinis, Stephen G. (Relations Industrielles / Industrial Relations, 1983)
The author presents the results of a survey on the attitude of trade unions towards technological change.

La sélection des cadres : principes et problèmes contemporains - Pettersen, Normand (Relations Industrielles / Industrial Relations, 1983)
This article reviews the book, "La sélection des cadres : principes et problèmes contemporains," by Shimon Dolan & Denis Roy.

More Than A Labour of Love: Three Generations of Women's Work in the Home - Pierson, Ruth Roach (Labour / Le Travail, 1983)
This article reviews the book, "More Than A Labour of Love: Three Generations of Women's Work in the Home," by Meg Luxton.

The Inquisition in Hollywood: Politics in the Film Community, 1930-1960; Film on the Left: American Documentary Film from 1931 to 1942 - Pierson, Stuart (Labour / Le Travail, 1983)
This article reviews two books: "The Inquisition in Hollywood: Politics in the Film Community, 1930-1960," by Larry Ceplair and Steven Englund, "Film on the Left: American Documentary Film from 1931 to 1942," by William Alexander.

" The Bonds of Unity": A Comment - Piva, Michael (Histoire sociale/Social History, 1983)
Disputes the statistics regarding the proportion of the Ontario working population that the Knights of Labor represented, as given in the article, "The Bonds of Unity," by Gregory Kealey and Bryan Palmer.

Science and the Labour Process - Price, Richard (Labour / Le Travail, 1983)
The article reviews and comments on "Technology and Toil," by Maxine Berg, "Microelectronics: Capitalist Technology and the Working Class," by CSE Microelectronics Group, "Science, Technology and the Labour Process," edited by Les Levidow and "Living Thinkwork: Where Do Labour Processes Come From?," by Bob Young.

La responsabilité fonctionnelle chez les cadres subalternes. Facteur d’évolution des systèmes d’autorité - Rainville, Jean-Marie (Relations Industrielles / Industrial Relations, 1983)
Cet article présente le fonctionnement des rapports d'autorité entre des cadres subalternes et leurs supérieurs dans la section psychiatrique d'un hôpital montréalais.

French Canadian Immigrants in the New England Cotton Industry: A Socioeconimic [Socioeconomic] ]Profile - Ramirez, Bruno (Labour / Le Travail, 1983)
Analyzes changes in French Canadian immigration to the New England cotton industry from 1900-29. Documents the slow-down in immigration flow after 1900, the low presence of newly arrived immigrants, and a sharp decline in the proportion of second-generation as compared to first-generation immigrants who were working in the textile mills. Concludes that the French Canadian immigrants were a much more stable workforce component than previously assumed, and that the industry appears not to have been as attractive to immigrants as it had been during the 1879-90 period.

Maisonneuve - Comment des promoteurs fabriquent une ville - Ramirez, Bruno (Labour / Le Travail, 1983)
This article reviews the book, "Maisonneuve – Comment des promoteurs fabriquent une ville," by Paul-André Linteau.

Confessions of an Immigrant's Daughter - Repo, Satu (Labour / Le Travail, 1983)
This article reviews the book, "Confessions of an Immigrant's Daughter," by Laura Goodman Salverson.

Ideologies in Quebec: The Historical Development - Resnick, Philip (Labour / Le Travail, 1983)
This article reviews the book, "Ideologies in Quebec: The Historical Development," by Denis Monière.

Women, War, and Work: The Impact of World War I on Women Workers in the United States - Roberts, Barbara (Labour / Le Travail, 1983)
This article reviews the book, "Women, War, and Work: The Impact of World War I on Women Workers in the United States," by Maureen Weiner Greenwald.

Applied Human Relations, An Organizational Approach - Rondeau, Alain (Relations Industrielles / Industrial Relations, 1983)
This article reviews the book, "Applied Human Relations, An Organizational Approach," by Jack Halloran.

Le militantisme des travailleurs au Québec et en Ontario, niveau de syndicalisation et mouvement de grèves (1900-1980) - Rouillard, Jacques (Revue d'histoire de l'Amérique française, 1983)

The Voyage of the Komagata Maru: The Sikh Challenge to Canada's Colour Bar - Roy, Patricia E. (Labour / Le Travail, 1983)
This article reviews the book, "The Voyage of the Komagata Maru: The Sikh Challenge to Canada's Colour Bar," by Hugh Johnston.

Life, Work, and Rebellion in the Coal Fields: The Southern West Virginia Miners, 1880-1922 - Seager, Allen (Labour / Le Travail, 1983)
This article reviews the book, "Life, Work, and Rebellion in the Coal Fields: The Southern West Virginia Miners, 1880-1922," by David Alan Corbin.

Solitary Comrade: Jack London and His Work - Seretan, L. Glen (Labour / Le Travail, 1983)
This article reviews the book, "Solitary Comrade: Jack London and His Work," by Joan D. Hedrick.

Code du travail F.M., lois connexes et règlements - Sexton, Jean (Relations Industrielles / Industrial Relations, 1983)
This article reviews the book, "Code du travail F.M., lois connexes et règlements," by Les éditions FM à feuilles mobiles Enr.

Les licenciements collectifs au Québec : un bilan partiel du dispositif public en vigueur - Sexton, Jean (Relations Industrielles / Industrial Relations, 1983)
This article reviews the book, "Les licenciements collectifs au Québec : un bilan partiel du dispositif public en vigueur," by École de relations industrielles.

French Peasants in Revolt: The Insurrection of 1851 - Simoni, Pierre (Labour / Le Travail, 1983)
This article reviews the book, "French Peasants in Revolt: The Insurrection of 1851," by Ted W. Margadant.

The Economics of Mileage Restrictions for Railway Workers in Western Canada - Simpson, Wayne; Peters, Frank (Relations Industrielles / Industrial Relations, 1983)
The purpose of this paper is to examine the economics of the mileage payment System, to understand the problems created for the union and C.P.R. management and to examine potential solutions to the problem.

Housewife or Harlot: The Place of Women in French Society - Smith, Bonnie G. (Labour / Le Travail, 1983)
This article reviews the book, "Housewife or Harlot: The Place of Women in French Society," by James F. McMillan.

Mechanics and Manufacturers in the Early Industrial Revolution: Lynn, Massachusetts - Stern, Mark J. (Labour / Le Travail, 1983)
This article reviews the book, "Mechanics and Manufacturers in the Early Industrial Revolution: Lynn, Massachusetts," by Paul G. Faler.

Brothers Beyond the Sea: National Socialism in Canada - Stokes, Lawrence D. (Labour / Le Travail, 1983)
This article reviews the book, "Brothers Beyond the Sea: National Socialism in Canada," by Jonathan F. Wagner.

Beyond Her Sphere: Women and the Professions in American History; Women's Work and Family Values 1920-1940; Beyond Suffrage: Women in the New Deal - Strong-Boag, Veronica (Labour / Le Travail, 1983)
This article reviews three books: "Beyond Her Sphere: Women and the Professions in American History," by Barbara J. Harris, "Women's Work and Family Values, 1920-1940," by Winifrid Wandersee, and "Beyond Suffrage: Women in the New Deal," by Susan Ware.

Along the No. 20 Line : Reminiscences of the Vancouver Waterfront - Synge, Jane (Labour / Le Travail, 1983)
This article reviews the book, "Along the No. 20 Line : Reminiscences of the Vancouver Waterfront," by Rolf Knight.

Fragile Freedoms: Human Rights and Dissent in Canada - Thompson, David L. (Labour / Le Travail, 1983)
This article reviews the book, "Fragile Freedoms: Human Rights and Dissent in Canada," by Thomas R. Berger.

Trade Unions in Canada : 1812-1902 - Thwaites, James (Relations Industrielles / Industrial Relations, 1983)
This article reviews the book, "Trade Unions in Canada: 1812-1902," by Eugene Forsey.

La grève des ouvriers de la construction navale à Québec (1840) - Tremblay, Robert (Revue d'histoire de l'Amérique française, 1983)

The United Brotherhood of Railway Employees in Western Canada, 1898-1905 - Tuck, J. Hugh (Labour / Le Travail, 1983)
This essay examines the rise and fall in the Canadian West of the United Brotherhood of Railway Employees (UBRE), an industrial union similar to the American Railway Union of the early 1890s. The UBRE entered Canada in 1902, but was unable to disrupt the complex network of craft union organizations which had sprung up in Canada in the preceding decade. It was, as a consequence, largely restricted to organizing previously unorganized clerks, freight handlers, and labourers. It fought a marginally successful strike on the Canadian Northern Railway in 1902, but was defeated by the CPR in 1903. This latter defeat, which had been engineered by the company with the aid and approval of the craft unions and the Canadian government, contributed directly to the rapid decline and ultimate demise of the UBRE. This ended the last major attempt to organize North American railway workers on industrial rather than craft lines.

Assault on the Worker: Occupational Health and Safety in Canada - Tucker, Eric (Labour / Le Travail, 1983)
This article reviews the book, "Assault on the Worker: Occupational Health and Safety in Canada," by Charles E. Reasons, Lois L. Ross, and Craig Paterson.

The Politics of Federalism: Ontario's Relations with the Federal Government 1867-1942 - Tupper, Allan (Labour / Le Travail, 1983)
This article reviews the book, "The Politics of Federalism: Ontario's Relations with the Federal Government 1867-1942," by Christopher Armstrong.

Politics and Ideology in the Age of the Civil War - Twomey, Richard (Labour / Le Travail, 1983)
This article reviews the book, "Politics and Ideology in the Age of the Civil War," by Eric Foner.

Les mutations chez les infirmières et les infirmiers - Veilleux, Diane (Relations Industrielles / Industrial Relations, 1983)
Cet article vise à établir comment la promotion et la mutation chez les infirmiers(ères) sont encadrées par les conventions collectives et par les spécificités de la profession exercée.

À l’enseigne du droit social belge - Verge, Pierre (Relations Industrielles / Industrial Relations, 1983)
This article reviews the book, "À l’enseigne du droit social belge," by l’Université de Bruxelles, edited.

A Primer on American Labor Law - Verge, Pierre (Relations Industrielles / Industrial Relations, 1983)
This article reviews the book, "A Primer on American Labor Law," by W.B. Gould.

L’obligation de paix du travail – étude du droit suisse et comparé - Verge, Pierre (Relations Industrielles / Industrial Relations, 1983)
This article reviews the book, "L’obligation de paix du travail – étude du droit suisse et comparé," by Gabriel Aubert.

Labour Law and Industrial Relations: Building on Kahn-Freund - Verge, Pierre (Relations Industrielles / Industrial Relations, 1983)
This article reviews the book, "Labour Law and Industrial Relations: Building on Kahn-Freund," by Lord Wedderburn of Charlton, R. Lewis & J. Clark, edited.

Syndicalisation de la grève - Verge, Pierre (Relations Industrielles / Industrial Relations, 1983)
Initialement affirmé en fonction des individus qui se coalisent, le droit de grève envisagé par le Code du travaildu Québec s'« acquiert » par l'association accréditée. L'auteur s'interroge sur les conséquences juridiques d'une telle dissociation du droit de grève des individus qui participent au mouvement collectif: limites de la liberté des salariés; responsabilité de l'instance syndicale à l'occasion des grèves illégales, de même que celle des grévistes eux-mêmes; enfin, la situation particulière des salariés qui ont assumé des charges au sein de l'association accréditée.

Scientific Management, Job Redesign and Work Performance - Vinet, Alain (Relations Industrielles / Industrial Relations, 1983)
This article reviews the book, "Scientific Management, Job Redesign and Work Performance," by John E. Kelly.

Corporatism, Participation and Society - Warner, Malcolm (Relations Industrielles / Industrial Relations, 1983)
After having located industrial democracy within the broader debate on corporatism, the author examines the attempts made to institutionalize developments of industrial democracy.

Going for Coffee: Poetry on the Job - Watt, F.W. (Frank William) (Labour / Le Travail, 1983)
This article reviews the book, "Going for Coffee: Poetry on the Job," edited by Tom Wayman.

Inside Job: The Transformation of Literature - Wayman, Tom (Labour / Le Travail, 1983)
Argues that the centrality of daily work in human existence should make it a fundamental dimension of imaginative literature. The author discusses his commitment to writing about work from an inside-the-job perspective, and critiques other forms of fiction. Offers a definition of the "new industrial literature," including that it must help alter reality for the better. Considers aspects of new work writing (including in work poetry), writing as a skill, and the work-writing movement.

Paper, Scissors, Stone [work poem] - Wayman, Tom; Grierson, Al; Cudney, Bruce; McClung, Nellie; Shreve, Sandra; Priest, Alicia; Mouré, Alain; Cathers, Ken; Ommer, Rosemay E. (Labour / Le Travail, 1983)
Presents work poetry including "Paper, Scissors, Stone" and "The Detroit State Poems: Final Day" by Tom Wayman; "Waiting for Them to Come Back from Coffee" by Bruce Cudney; "Sorting Mail at Xmas" by Nellie McClung;; "job description" by Alicia Priest; "It's All Our Fault" by Al Grierson; "What He Knew" and "We are a Trade" by Alain Mouré; "The Strait of Belle Isle" by Rosemary E. Ommer; "Telephone Operator" by Sandra Shreve; and "give away" by Ken Cathers.

Du concept de « professionnalité » dans les relations industrielles italiennes - Weiss, Dimitri (Relations Industrielles / Industrial Relations, 1983)
Après avoir fait le tour des significations le plus souvent attribuées au concept, typiquement italien, de professionnalité, qui engendre des prises de positions multiples des partenaires sociaux et un discours envahissant, original mais non privé de rhétorique, des observateurs du système de relations industrielles, l'auteur livre quelques observations autour du thème choisi, qui ne se confond pas toujours avec le « professionnalisme », tel que ce vocable est employé respectivement en anglais et en français.

Le coeur à l’ouvrage - Weiss, Dimitri (Relations Industrielles / Industrial Relations, 1983)
This article reviews the book, "Le coeur à l’ouvrage," by Gérard Lefebvre.

Les cadres : la formation d’un groupe social ; Politique d’éducation et organisation industrielle en France et en Allemagne : essai d’analyse sociétale - Weiss, Dimitri (Relations Industrielles / Industrial Relations, 1983)
This article reviews the book, "Les cadres : la formation d’un groupe social," by Luc Boltanski. This article reviews the book, "Politique d’éducation et organisation industrielle en France et en Allemagne : essai d’analyse sociétale," by M. Maurice, F. Sellier & J.J. Silvestre

Les syndicats dans la société française ; I sindacalisti - Weiss, Dimitri (Relations Industrielles / Industrial Relations, 1983)
This article reviews the books, "Les syndicats dans la société française," by René Mouriaux This article reviews the book, "I sindacalisti," by Gloria Pirzio Ammassari & Francesco Mattioli.

Poverty, Distress, and Disease: Labour and the Construction of the Rideau Canal, 1826-32 - Wylie, William N.T. (Labour / Le Travail, 1983)
The construction of The Rideau Canal was one of the first projects in Upper Canada to employ thousands of wage-earners. While this was a British military undertaking, the officers and the contractors they hired shared a common attitude to workers: they were viewed primarily as instruments of production required to facilitate the most economic completion of the project. Because of an unfavourable labour market, labourers were forced to endure difficult and often dangerous working and living conditions. The response of workers to these conditions was militant but sporadic. They tended to act against individual property owners and contractors in order to obtain the immediate necessities for survival. More concerted activity was discouraged in large part by the military which posted soldiers along the line of the canal to suppress dissent and ensure a cheap supply of labour.

Behavioural Science Application in Vancouver Based Firms - Xishan, Yang; Moore, Larry F.; Markgraf, Herb (Relations Industrielles / Industrial Relations, 1983)
This study aims first at identifying the state of the art of behavioural science applications and its achievements in Western Canada and at reflecting the different views of various parties towards behavioural science so as to help determine the applicability and practical value of behavioural science in the field of management.

U.S. Industrial Relations 1950-1980 : A Critical Assessment, Edited by Jack Stieber, Robert B. McKersie and D. Quinn Mills - Zaidi, Mahmood A. (Relations Industrielles / Industrial Relations, 1983)
This article reviews the book, "U.S. Industrial Relations 1950-1980: A Critical Assessment," by Jack Stieber, Robert B. McKersie & D. Quinn Mills, edited.